2020
DOI: 10.3390/pr8080986
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Multiwall Carbon Nanotube Decorated with Novel Functionalities: Synthesis and Application as Adsorbents for Lead Removal from Aqueous Medium

Abstract: Water pollution is one of the major challenges facing modern society because of industrial development and urban growth. This study is directed towards assessing the use of multiwall carbon nanotube, after derivatization and magnetization, as a new and renewable absorbent, to remove toxic metal ions from waste streams. The adsorbents were prepared by, first oxidation of multiwall carbon nanotube, then derivatizing the oxidized product with hydroxyl amine, hydrazine and amino acid. The adsorbents were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The kinetics and mechanism of SMZ adsorption on 3D GF-CS have been studied using pseudo-first-order and pseudo-secondorder models (Hanbali et al, 2020a;Hanbali et al, 2020b). In separate 250-ml Erlenmeyer flasks, 50 ml of different beginning SMZ concentrations (50,100,200,300, and 400 mgL −1 ) were created; then, specified adsorbate masses were added and incubated for 20 min at 25 °C and 200 rpm.…”
Section: Adsorption Kinetics Studiesmentioning
confidence: 99%
“…The kinetics and mechanism of SMZ adsorption on 3D GF-CS have been studied using pseudo-first-order and pseudo-secondorder models (Hanbali et al, 2020a;Hanbali et al, 2020b). In separate 250-ml Erlenmeyer flasks, 50 ml of different beginning SMZ concentrations (50,100,200,300, and 400 mgL −1 ) were created; then, specified adsorbate masses were added and incubated for 20 min at 25 °C and 200 rpm.…”
Section: Adsorption Kinetics Studiesmentioning
confidence: 99%
“…The results indicate that the competitive adsorption between the other cationic ions existing in tap water and RhB on F‐MoO 3 nanosheets led to the reduction of the adsorption capacity. [ 61 ] Although the adsorption performance decreased in the stimulated real water, the adsorption capacity (416 mg g −1 , RhB/F‐MoO 3 nanosheets) is still much higher than other currently reported MoO 3 materials (Table 1), showing great potential in industrial dye removal.…”
Section: Resultsmentioning
confidence: 95%
“…Meanwhile, the adsorption capacity of RhB on F‐MoO 3 nanosheets decreased in real water, due to the negatively charged active binding sites being partly occupied by the other cationic ions in tap water. [ 61 ] Besides, the anionic dye (reactive black 5) was tested to verify if the RhB dye was adsorbed on F‐MoO 3 nanosheets via electrostatic attractions. As shown in Figure S8 (Supporting Information), the concentration of the solution barely decreased after the adsorption, demonstrating that the negatively charged F‐MoO 3 nanosheets can hardly adsorb anionic dyes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the results of the BET surface area examination of MWCNTs show that the whole surface area was observed to be 180.89 m 2 g −1 . It was shown that the MWCNTs have a greater specific surface area than that distinguished by Hanbali et al [37]. The specific surface area of MWCNTs is affected by their agglomeration, attendance of impurities, diameter, surface functionalization, etc.…”
Section: Bet Analysismentioning
confidence: 93%